Kesantunan Berbahasa Anak melalui Novel Mata dan Nyala Api Purba Karya Okky Madasari - Kurniawan, Ade; Puspitasari, Nur Aini (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The purpose of this study was to describe children's language politeness in the maxims of reading, acceptance, humility, sympathy, agreement, and generosity. This study used descriptive qualitative method. The data collection procedures in this study include: prevention, reading novels of the eye and ancient flame which carry maxims repeatedly, inventorying dialogues of children and main characters containing maxims, data collection, data analysis, and interpreting data. The data analysis technique in this study used content analysis with the steps of reading and classifying the types of maxims. The results of this study show politeness in children's language, the maxim of sympathy with the indicator showing sympathy for the speech partner, the maxim above the indicator does not cause harm to the speech partner, the maxim of humility with the type of praising the speech partner and one's own goals as much as possible and the maxim of error with the type of understanding agreement. others and maximize approval of others. The importance of language politeness in novels and daily life, this research can be used as language learning for children.